2020
DOI: 10.3390/pathogens9090767
|View full text |Cite
|
Sign up to set email alerts
|

Does Curcumin Have a Role in the Interaction between Gut Microbiota and Schistosoma mansoni in Mice?

Abstract: There is strong correlation between changes in abundance of specific bacterial species and several diseases including schistosomiasis. Several studies have described therapeutic effects of curcumin (CUR) which may arise from its regulative effects on intestinal microbiota. Thus, we examined the impact of CUR on the diversity of intestinal microbiota with/without infection by Schistosoma mansoni cercariae for 56 days. Enterobacteriaceae was dominating in a naive and S. mansoni infected mice group without CUR tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Evidence suggests that gut microbiota composition is associated with Schistosoma mansoni infection burden in rodent models (Cortes et al, 2020). Our previous work and other reports revealed that schistosome infection decreases the alpha diversity and richness of beneficial bacteria of gut microbiota in mammals such as rodents (Anter et al, 2020;Cortes et al, 2020;Jenkins et al, 2018;Song et al, 2020;Zhang B. et al, 2020) and humans (Gui et al, 2021;Kay et al, 2015). Lack of host gut microbiota alters host immune responses to intestinal granuloma formation and hepatic fibrosis in infected mice (Holzscheiter et al, 2014).…”
mentioning
confidence: 85%
“…Evidence suggests that gut microbiota composition is associated with Schistosoma mansoni infection burden in rodent models (Cortes et al, 2020). Our previous work and other reports revealed that schistosome infection decreases the alpha diversity and richness of beneficial bacteria of gut microbiota in mammals such as rodents (Anter et al, 2020;Cortes et al, 2020;Jenkins et al, 2018;Song et al, 2020;Zhang B. et al, 2020) and humans (Gui et al, 2021;Kay et al, 2015). Lack of host gut microbiota alters host immune responses to intestinal granuloma formation and hepatic fibrosis in infected mice (Holzscheiter et al, 2014).…”
mentioning
confidence: 85%
“…When the liver is continually exposed to metabolites of intestinal microbiota, TLRs are activated in target cells by lipopolysaccharides and induce inflammatory signaling pathways that lead to repeated damage to liver cells, subsequently causing liver fibrosis, cirrhosis, and even hepatocellular carcinoma ( Yooseph et al, 2015 ; Zhou et al, 2017 ). Anter et al (2020) found that there is a correlation between curcumin dosages and the species of gut microbiota in mice infected with S. mansoni .…”
Section: Introductionmentioning
confidence: 96%